(untitled) (Proceedings of the International Conference on Education, 2021)
Innovation in learning and teaching in higher education permits greater impact on students in the context of the current form of communication. Compared to the traditional model of teaching. employing innovative teaching resources offers opportunities to explore different global perspectives and can help students recognize the complexities behind the world’s current challenges, including that of Sustainable Development. This study is part of an investigation that, through different methods has collected information to address the need for innovative resources to promote Sustainable Development Education (SDE) more efficiently into the higher education curricula, specifically into the Architecture and Design programs. This study seeks to respond to the call for responsible actions, based on rational principles and ethical values to integrate Sustainable Development (SD) in the study plans through the design of a digital platform and an online test that allows architecture and industrial design students to evaluate the sustainability of their projects. A survey was applied for the first time in June 2020 to a sample of 145 students from nine Project courses; the main results of this first application are presented in this paper. An important finding so far is that it is necessary to integrate SD more firmly and more efficiently and that a deeper reflection in students about SD must be promoted. It is also important to provide the students with an adequate variety of resources for the development of their projects, such as: tests to evaluate sustainability, links to workshops, online games, complementary courses and conferences, videos and webinars with experts, among others.